Knowledge sharing and innovation capabilities: The moderating role of organizational learning - Sulaman Hafeez Siddiqui; Rabia Rasheed; Shahid Nawaz; Mazhar Abbas (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
The main purpose of this research is to analyze those factors that affect the knowledge sharing and can lead the conventional banking sector towards enhancing the innovation capabilities by creating the culture of organizational learning. The model of this research paper is tested using a sample of 300 employees occupying the position of officer grade I, II and III in conventional banking sector of Bahawalpur. Researchers have used the simple random sampling technique for the collection of data with the help of questionnaire. SPSS version 21 is used to analyze data collected for this research paper. The result shows that out of nine factors, seven factors namely individual personality, individual attitude, reward and recognition, competence based trust, benevolence based trust, ICT infrastructure and availability and ICT know how are all significantly and positively related with the innovation capabilities as well as knowledge sharing and thus knowledge sharing also mediates between them. But the two factors centralization and formalization have an insignificant relationship with the innovation capabilities and knowledge sharing. Hence, no mediation takes place between them. Moderator; organizational learning also plays a significant role between knowledge sharing and innovation capabilities. This research paper has a significant managerial implication that it helps the managing bodies of conventional banks to pay an attention on these factors like individual personality, individual attitude, reward and recognition, competence based trust, benevolence based trust, ICT infrastructure and availability and ICT know how in order to enhance the innovation capabilities. The incorporation of individual personality, individual attitude, reward and recognition, competence based trust, benevolence based trust, ICT infrastructure and availability and ICT know how in order to enhance the innovation capabilities. Model offers a new theoretical lens and an alternative explanation for the determinants influencing the knowledge sharing that leads to innovation capabilities.
Keywords: 330; competence based trust; benevolence based trust; ICT know how; organizational learning; innovation capabilities; banking sector